Transfer of passive immunity and serum proteinogram in calves of the Criollo Lageano hornless variety and Aberdeen Angus (Red Angus) breed in their first six months of life Transferência de imunidade passiva e proteinograma sérico em bezerros das raças Crioula Lageana variedade Mocha e Aberdeen Angus (Red Angus) nos primeiros seis meses de vida - Schade J.* (2016)
© 2016, Colegio Brasileiro de Patologia Animal.The Criollo Lageano breed is an alternative for modern farming, due to its high genetic variability, rusticity and adaptation to environmental conditions of the Plateau of Santa Catarina, Brazil. These characteristics can influence important physiological events which should be investigated, because they can assist in developing future programs of animal breeding. It is known that failure of passive transfer (FPT) is an important factor for the increase in neonatal mortality in cattle. Thus, it is essential to evaluate aspects related to FPT in Criollo Lageano calves and the comparison with other beef breed created in the Plateau of Santa Catarina. Aiming to evaluate and to compare the passive transfer of immunity and serum protein concentrations, two experimental groups of 11 calves of Criollo Lageano (CL) hornless variety and 14 Aberdeen Angus (Red Angus) calves were selected. Blood samples were collected by jugular venipuncture for the measurement of total serum protein (TSP) by serum protein electrophoresis in agarose gel and the activity of gamma glutamyl transferase (GGT) and concentration of immunoglobulin G (IgG) by the method of the turbidity zinc sulphate, between 24 and 36 hours, 15, 30, 60, 90, 120, 150 and 180 days. Statistical analysis of data was performed by analysis of variance (ANOVA), Tukey test for comparison of means (P < 0.05) and correlation between variables. Values of TSP, globulins, immunoglobulins, IgG and serum GGT activity at birth (24-36 hours) confirmed that there was adequate TIP with no significant difference between the races, except for the serum GGT activity. Physiological variations in the curve of serum proteins from birth to 180 days of age were identified. Strong positive correlation was found between the values of gamma imunoglobuliglobulin and IgG (r=0.814 and r=0.877 for CL to AA), PTS (r=0.783 and r=0.947 for CL to AA), globulins (r=0.945 and r=0.985 for CL to AA), indicating that these variables will be good indicators of TIP in calves at the second day of life (24-36 hours). The correlation between gamma globulin and activity of GGT was weakly positive (r=0.251) for CL and strongly positive (r=0.815) for the Aberdeen Angus (Red Angus), in which a wide variation in GGT values after 24 hours of life of the calf were noticed. No difference was found in FPT between Criollo Lageano hornless variety and Aberdeen Angus (Red Angus), and was successful way in both breeds. It can be suggested that Criollo Lageano hornless variety breed is later in active antibody synthesis, highlighting the precocity of taurine evident in Aberdeen Angus (Red Angus) breed.